Theoretical studies on bimolecular reaction dynamics. - Clary, D (2008)
This perspective discusses progress in the theory of bimolecular reaction dynamics in the gas phase. The examples selected show that definitive quantum dynamical computations are providing insights into the detailed mechanisms of chemical reactions.